Australian Journal of Advanced Nursing June - August 2015 Vol.32 No.4 - Redaksi (Australian Nursing Federation, 2015)
- Doctoral theses in nursing and midwifery: challenging their contribution to nursing scholarship and the profession - Registered nurses improving screening rates for non AIDS related comorbidities in people living with HIV - Enhancing the online learning experience using virtual interactive classrooms - A nurses communication manager reduces non relevant contacts - Advanced skills for enrolled nurses : a developing classification